2020
DOI: 10.1039/d0dt02162h
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-directed fabrication of three polyoxovanadate-based copper frameworks as efficient catalysts for constructing C–N bonds

Abstract: The first synthetic pathway for the directed preparation of three novel polyoxovanadates-based copper frameworks (POVCFs), i.e., [Cu0.5(1-ipIM)2]2[V4O11] (POVCFs 1) and [Cu(1-ipIM)2](VO3)2 (POVCFs 2) and [Cu(1-pIM)4](HpIM)4[V10O28] (POVCFs 3) (1-ipIM = 1-isopropylimidazole;...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The eight terminal V=O t bond lengths are the smallest ones with values in the range of 1.6033(19)-1.6111(18) Å. Lastly, the V-V distances are between 3.1053 (6) and 3.0171 (6) Å. The bond distances are similar to [V 10 O 28 ] 6− units found in the literature (Kumagai et al, 2002;Huang et al, 2020). The excellent quality of X-ray diffraction data allowed to localize the hydrogen atoms within the decavanadate cluster in O10 atom, led by an inversion center to diprotonated decavanadate units [H 2 V 10 O 28 ] 4− .…”
Section: Crystalsupporting
confidence: 78%
See 1 more Smart Citation
“…The eight terminal V=O t bond lengths are the smallest ones with values in the range of 1.6033(19)-1.6111(18) Å. Lastly, the V-V distances are between 3.1053 (6) and 3.0171 (6) Å. The bond distances are similar to [V 10 O 28 ] 6− units found in the literature (Kumagai et al, 2002;Huang et al, 2020). The excellent quality of X-ray diffraction data allowed to localize the hydrogen atoms within the decavanadate cluster in O10 atom, led by an inversion center to diprotonated decavanadate units [H 2 V 10 O 28 ] 4− .…”
Section: Crystalsupporting
confidence: 78%
“…Vanadium compounds can also be used in a wide variety of catalytic processes, and many research papers and reviews on specific themes of vanadium catalysts have lately been published ( Huang et al, 2020 ; Sutradhar et al, 2020 ). Decavanadates have a wide range of applications in biology; however, several papers have shown that they can also work as a catalyst ( Hill and Bouchar, 1985 ; Steens et al, 2010 ; Foster et al, 2011 ) and recently for the photochemical oxidation of water to dioxygen ( Buvailo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of title hybrid dipyridylaminepolyoxovanadates is shown in the figure. Single crystal diffraction analysis of the title compound revealed that it Atom [12][13][14]. Each dpa ligand has a protonated hydrogen atom on the nitrogen of pyridinyl moiety.…”
Section: Commentmentioning
confidence: 99%
“…Polyoxovanadates (POVs), are a class of vanadium-oxide clusters with reversible multi-electron redox transformations under mild conditions, which allow them to act as multi-functional catalysts in homogeneous or heterogeneous catalytic systems [3][4][5][6]. The functionalization of the POVs cluster can endow them more properties and thus exploration of new functionalized POVs structure is an interesting aspect in recent POVs chemistry [7,8].…”
Section: Commentmentioning
confidence: 99%